Pengaruh Inflasi dan Suku Bunga terhadap Harga Saham Pada Perusahaan Perbankan yang Terdaftar di BEI - Sindy Iradilah; Ahmad Albar Tanjung (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
The capital market is one of the drivers of a country’s economy, stocks are one of the most preferred investments by investors in the capital market. The purpose of this study is to determine whether there is an effect of inflation and interest rates on stock prices in banking companies listed on the Indonesia Stock Exchange. This research was conducted at PT. Bank Mandiri (Persero), Tbk, this study used data every month in the period January 2014 to December 2021, the data analysis method used in this study was descriptive quantitative, while the analysis model used in this study was linear regeression analysis multiple. The result of this study indicate that partially inflation has no and no significant effect on stock prices, while interest rates have a negative and significant effect on stock prices. Meanwhile, simultaneously inflation and interest rates affect stock prices. With the interest rate factor that has a negative effect, it will be taken into consideration for the company and the monetary authority in the determining the share price of the company.